Quantifying the composition of yttrium and oxygen rich nanoparticles in oxide dispersion strengthened steels. - Williams, C; Smith, G; Marquis, E (2013)
Atom probe tomography (APT) is used to investigate the composition of oxygen rich nanoparticles within a ferritic matrix in Fe-14Cr-2W-0.1Ti oxide-dispersion-strengthened (ODS) steel. This study investigates whether artifacts associated with APT analysis are the cause of a sub-stoichiometric oxide composition measurement. Bulk Y₂O₃ is analyzed by APT, thus demonstrating the ability of the technique to measure near-stoichiometric composition measurements in insulating oxides. Through analysis of the sequence of ion hits on the detector during APT data acquisition, it is shown that a proportion of yttrium hits are spatially correlated but oxygen hits are not. Y-O based nanoparticles in a ferritic matrix are analyzed by APT using voltage pulsing and a laser pulsing with a range of laser energies from 0.3-0.8 nJ. When the material is analyzed using a high effective evaporation field, this influences the effect of trajectory aberrations, and the apparent size of the nanoparticles is reduced. Some reduction in Y:O ratio is observed, caused by high instances of multiple-ion evaporation events. From a detailed comparison between the results of APT analysis of the bulk Y₂O₃ the nanoparticles in the ODS material are concluded to have an approximate Y:O ratio of 1:1.